Bilayer orthogonal ferromagnetism in CrTe2-based van der Waals system - Bigi, Chiara; Jego, Cyriack; Polewczyk, Vincent; De Vita, Alessandro; Jaouen, Thomas; Tchouekem, Hulerich C.; Bertran, François; Le Fèvre, Patrick; Turban, Pascal; Jacquot, Jean-François; Miwa, Jill A.; Clark, Oliver J.; et al. (Nature communications, 2025)
Systems with pronounced spin anisotropy are pivotal in advancing magnetization switching and spin-wave generation mechanisms that are fundamental to spintronic technologies. Quasi-van der Waals ferromagnets like Cr 1+ δ Te 2 represent seminal materials in this field, renowned for their delicate balance between frustrated layered geometries and magnetism. Despite extensive investigation, the nature of their magnetic ground state and the mechanism of spin reorientation under external fields and varying temperatures remain contested. Here, we exploit complementary techniques to reveal a previously overlooked magnetic phase in Cr 1+ δ Te 2 ( δ = 0.25 − 0.50), which we term orthogonal-ferromagnetism. This phase consists of atomically sharp single layers of in-plane and out-of-plane maximally canted ferromagnetic blocks, which differs from the stacking of multiple heterostructural elements required for crossed magnetism. Contrary to earlier reports of gradual spin reorientation in CrTe 2 -based systems, we present evidence for abrupt spin-flop-like transitions. This discovery further highlights Cr 1+ δ Te 2 compounds as promising candidates for spintronic and orbitronic applications, opening new pathways for device engineering. Self-intercalated Chromium tellurides consist of CrTe 2 van der Waals layers, with additional Chromium atoms residing in the van der Waals gap. This highly tuneable class of magnetic materials has presented a range of unique magnetic phenomena, and here Bigi, Jego, Polewczyk et al add to this by showing that CrTe 2 ( δ = 0.25 − 0.50) hosts orthogonal ferromagnetism.